Peranan Muhadhoroh Dalam Meningkatkan Kemampuan Public Speaking Santri di Pesantren Al Misbah Kota Tasikmalaya - Rifyal Luthfi (INTEGRATIF |Jurnal Magister Pendidikan Agama Islam, 2023)
Public speaking is the process of speaking to a group of people in a structured way that is deliberately intended to inform, influence, or entertain listeners. Public speaking is not an easy task, it requires good language skills. Fear and anxiety are a big problem, especially for beginners who have no experience in public speaking Pst. Al Misbah Tasikmalaya city. This also happens to students. Their language competence is in adequate. That is why muhadharah activities are held. This is expected to improve their skills.